LEGAL REASONING DISSENTING OPINION HAKIM DALAM PENERAPAN PASAL 2 AYAT 1 UU TPPO PADA PROSTITUSI ANAK - Desy Ervitasari; Riri Tri Mayasari (UNIB Press, 2025)
This research examines the disparities in legal reasoning within the Manna District Court Decision Number 00/Pid.Sus/2025/PN Mna regarding the application of Article 2, Paragraph 1 of the Law on the Eradication of the Crime of Trafficking in Persons (TIP Law) in cases of child prostitution. The central legal issue lies in the conflicting interpretations of the elements of